The system and spatial distribution of protected areas in Hungary, Slovakia, Romania, Serbia and Croatia - Mari, László; Tábori, Zsófia; Šulc, Ivan; Radeljak KaufmannPetra; Milanović, Ranko; Gessert, Alena; Imecs, Zoltán; Baricz, Anetta; Telbisz, Tamás (Hungarian Geographical Bulletin, 2022)
Protected areas play a key role in nature conservation but are also crucial for tourism. There are international recommendations in nature conservation (IUCN), and several international conservation conventions exist. Nevertheless, the protection categories are different in each country, and the proportion of protected areas also varies. Here we compare the nature conservation systems of some countries (Hungary, Slovakia, Romania, Serbia and Croatia) taking into consideration their nature protection laws. The selection of countries is based on an international project dealing with “Karst and National Parks”. For the comparison, national data sources and an international database (WDPA) are used. Our results show that the protection categories of the studied countries are largely similar, but there are unique characteristics as well (such as “forest park”, “monument of park architecture” in Croatia; “nature conservation area” in Hungary or “protected landscape element” in Slovakia, etc.). On the other hand, the internal proportions of protection categories are more heterogeneous, like, for example, the proportion of national parks within all protected areas which is 57.0 percent in Hungary but 11 percent in Croatia. International protection categories (Natura 2000, Ramsar, UNESCO World Heritage natural sites, UNESCO MAB reserves) are more or less similarly present in the countries studied (except Serbia, where there are no Natura 2000 areas yet). If national categories and Natura 2000 sites are all taken into consideration (and the overlapping areas are counted only once), then Croatia has the highest proportion of protected areas (39.1%), Slovakia is in second place with 37.5 percent, while Romania (23.5%) and Hungary (22.0%) show a similar proportion, and with the lack of Natura 2000, Serbia has 9.1 percent at present. As for the reliability of the WDPA, we found that this varies from country to country, with significant deficiencies for certain countries (e.g. Serbia) and very good reliability for others (e.g. Hungary, Slovakia). However, the availability of WDPA is in many cases better than that of national data, and since it also provides GIS data, it can be considered a useful tool for examining international trends and mapping protected areas.